Ortho-para hydrogen conversion characteristics of amorphous and mesoporous Cr2O3 powders at a temperature of 77 K - Kim, Jung Hyun; Karng, Sarng Woo; Oh, In-Hwan; Nah, In Wook (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this study, mesoporous Cr2O3 catalysts are prepared by use of the hard template method using mesoporous silica (SBA-15) as template, the prepared catalysts were characterized, and investigated for ortho to para hydrogen. The Cr2O3 catalysts at post-treated temperature at 150 degrees C have the largest BET surface area of 230 m(2) g(-1), and the length and diameter of the particles are 2 mu m and 5 nm, respectively. The highest spin conversion from ortho to para hydrogen was observed for the mesoporous Cr2O3 catalysts with the largest surface area post-treated at 150 degrees C in the range from 150 to 300 degrees C. The nanowire array morphology of the powders was maintained at the post-treatment temperature ranges of 150 and 200 degrees C. However, when temperature increased up to 300 degrees C, the nanowire array morphology disappeared. It was showed that the spin conversion process was strongly dependent on various factors such as BET surface area, calcination temperature and morphology of mesoporous Cr2O3 catalysts. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: STORAGE; LIQUID